Hypervirulent Chlamydia trachomatis Clinical Strain Is a Recombinant between Lymphogranuloma Venereum (L2) and D Lineages - Naraporn Somboonna (American Society for Microbiology, 2011)
ABSTRACT Chlamydia trachomatis is an obligate intracellular bacterium that causes a diversity of severe and debilitating diseases worldwide. Sporadic and ongoing outbreaks of lymphogranuloma venereum (LGV) strains among men who have sex with men (MSM) support the need for research on virulence factors associated with these organisms. Previous analyses have been limited to single genes or genomes of laboratory-adapted reference strain L2/434 and outbreak strain L2b/UCH-1/proctitis. We characterized an unusual LGV strain, termed L2c, isolated from an MSM with severe hemorrhagic proctitis. L2c developed nonfusing, grape-like inclusions and a cytotoxic phenotype in culture, unlike the LGV strains described to date. Deep genome sequencing revealed that L2c was a recombinant of L2 and D strains with conserved clustered regions of genetic exchange, including a 78-kb region and a partial, yet functional, toxin gene that was lost with prolonged culture. Indels (insertions/deletions) were discovered in an ftsK gene promoter and in the tarp and hctB genes, which encode key proteins involved in replication, inclusion formation, and histone H1-like protein activity, respectively. Analyses suggest that these indels affect gene and/or protein function, supporting the in vitro and disease phenotypes. While recombination has been known to occur for C. trachomatis based on gene sequence analyses, we provide the first whole-genome evidence for recombination between a virulent, invasive LGV strain and a noninvasive common urogenital strain. Given the lack of a genetic system for producing stable C. trachomatis mutants, identifying naturally occurring recombinants can clarify gene function and provide opportunities for discovering avenues for genomic manipulation. IMPORTANCE Lymphogranuloma venereum (LGV) is a prevalent and debilitating sexually transmitted disease in developing countries, although there are significant ongoing outbreaks in Australia, Europe, and the United States among men who have sex with men (MSM). Relatively little is known about LGV virulence factors, and only two LGV genomes have been sequenced to date. We isolated an LGV strain from an MSM with severe hemorrhagic proctitis that was morphologically unique in tissue culture compared with other LGV strains. Bioinformatic and statistical analyses identified the strain as a recombinant of L2 and D strains with highly conserved clustered regions of genetic exchange. The unique culture morphology and, more importantly, disease phenotype could be traced to the genes involved in recombination. The findings have implications for bacterial species evolution and, in the case of ongoing LGV outbreaks, suggest that recombination is a mechanism for strain emergence that results in significant disease pathology.